INTERVENSI BERBASIS MINDFULNESS UNTUK ANAK DENGAN GANGGUAN EMOSI DAN PERILAKU: A SYSTEMATIC LITERATURE REVIEW - Rindia Nengsih; Marlina, Marlina; Elsa Efrina; Safaruddin, Safaruddin; Endang Sri Handayani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Emotional and Behavioral Disorders (EBD) in children are characterized by difficulties in emotion regulation, maladaptive behavior, and persistent social problems. Between 2015 and 2025, mindfulness-based interventions (MBIs) have been widely used to improve children's emotional and behavioral functioning. However, systematic evidence specifically examining the application of MBIs in children with EBD is still limited. Objective: This review aims to systematically review MBIs in children with EBD, focusing on the types of interventions, outcomes achieved, and current research trends. Methods: A systematic literature review was conducted following the PRISMA guidelines. A literature search was conducted in the Scopus database for articles published between 2015 and 2025. Inclusion criteria included published (peer-reviewed) empirical studies involving children with EBD as the main subjects and using structured MBIs. Data were extracted regarding study design, intervention type, duration, implementation location, and main findings. Results: A total of 16 articles met the inclusion criteria. Most interventions used Mindfulness-Based Stress Reduction (MBSR) and Mindfulness-Based Cognitive Therapy (MBCT) protocols implemented in schools and clinical settings. The review results showed improved emotion regulation, decreased aggressive or disruptive behavior, and improved social relationships. Interventions with longer durations and involving teachers or parents tended to produce more consistent positive effects. Conclusion: MBIs have the potential to be effective strategies for supporting the emotional and behavioral development of children with EBD. However, high-quality longitudinal research is needed to confirm long-term effectiveness and identify optimal implementation strategies.